Digital Branding Strategy in Food Trends to Grow Entrepreneur's Interest in Opening a Business (Study on Takoyaki & Okonomiyaki Kireidesu SME, East Jakarta) - Rd. D Lokita Pramesti Dewi; Jamalullail Jamalullail (Yayasan Ilomata, 2022)
Culinary, with various types of food and various menus, is now rife in the midst of society, especially during the current pandemic. It is added with the implementation of The Community Activities Restrictions Enforcement (CARE) by the government to limit the physical interaction between people and groups in an effort to reduce the transmission of COVID-19. With this implementation, the activities of people going out of the house are decreasing. This is what fosters public interest in buying food online. Companies that run online applications currently provide many attractive promos to attract the attention of consumers using their services. Marketing strategies and brands that exist in food trends businesses are diverse, in the current pandemic, there are many creative ideas for entrepreneurs to work with online culinary application service companies whose aim is to make it easier for consumers to buy food online. People who use this marketing and branding strategy also find it helpful because they don't need to leave the house to buy food, by using an application on their gadget the food will be delivered by an online motorcycle taxi driver (Ojol). Still because of the pandemic, many workers got laid off so many of them switch to opening a business, and most of the business they do is to open a contemporary culinary business. From the many culinary businesses that have sprung up, it also indirectly fosters the interest of entrepreneurs to open culinary businesses. The research method in this study used a qualitative descriptive with reference to the theory of Hierarchy Effect Models using the AIDA model as a stage of assistance in marketing targets to consumers. The source of the research data above was taken by using primary data (interviews and documentation). While the purpose of this study was to analyze the effect of the